Principles of Elemental Chemostratigraphy A Practical User Guide - Craigie, Neil (Advances in Oil and Gas Exploration & Production,, 2018)
This book provides the reader with a comprehensive understanding of the applications of chemostratigraphy. The first chapter of the book offers an introduction to the technique. This is followed by a chapter detailing sample preparation and analytical techniques. Chapter 3 focuses on the techniques utilised to establish the mineralogical affinities of elements, while the general principles of how to build a chemostratigraphic scheme are covered in Chapter 4. Chapters 5, 6 and 7 provide information on the applications of chemostratigraphy to clastic, carbonate and unconventional reservoirs respectively, and various case studies are presented. Wellsite applications, a discussion and conclusion section form the latter part of the book. The book will appeal to graduate and post graduate students of geology and professionals working in the hydrocarbon sector as a key reference text in chemostratigraphy.